Seismic Shot Point Navigation Data from the Bering Shelf and Chukchi Sea acquired during R/V Maurice Ewing expedition EW9410 (1994) (IEDA: Marine-Geo Digital Library, 2006)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9410 conducted in 1994 (Chief Scientist: Dr. Simon Klemperer). These data files are of ASCII format and include Seismic Shot Point Navigation data that provide the primary seismic navigation source for this cruise. Data were acquired as part of the project: Crustal Evolution of the Bering Shelf-Chukchi Sea, and funding was provided by NSF grants: EAR93-16573, EAR93-17087, EAR93-17142, and EAR93-17531.